Factors Related to Work Motivation of Volunteers at The Oepoi and Bakunase Public Health Center in Kupang City - Lidi, Bertila Silvia; Kenjam, Yoseph; Ndun, Helga J.N (Timorese Journal of Public Health, 2021)
Motivation is a driving force that can encourage someone to work effectively, cooperate and be integrated with all efforts in achieving good work performance. Motivation is influenced by the provision of incentives, social interaction at work, working environment conditions and rewards. The general objective of this study was to determine the factors related to the motivation of voluntary workers at the Oepoi and Bakunase Health Centers, Kupang City. The specific objective was to determine the level of work motivation, the relationship between the provision of incentives, social interaction at work, working environment conditions and rewards with the work motivation of volunteers at the Oepoi and Bakunase Health Centers, Kupang City. The type of research used is an analytic study using a cross-sectional study design. The population in this study were all voluntary workers at the Kupang City Health Center, amounting to 130 people spread over 11 health centers. The sample in this study were 41 volunteers, namely 21 people from the Oepoi Health Center and 20 people from the Bakunase Health Center. This sampling was seen from the highest number of voluntary at the Kupang City Health Center. The data obtained were analyzed descriptively and bivariately using the chi-square statistical test with a significance level of = 0.05. The results showed that all variables had a significant (significant) relationship with voluntary work motivation, namely the provision of incentives (ρ = 0.000), working environment conditions (ρ = 0.000), social interaction at work (ρ = 0.001) and rewards (ρ). =0.021). Public health center needs to pay attention to providing incentives so that they can meet basic needs, pay attention to safety, and the comfort of volunteers in working so that voluntary can work optimally.